(untitled) (Nexo Revista Científica, 2021)
In this study, a new method is introduced for stress data visualization. As an example, the SHmax variations in the Makran region are mapped by using this new approach. Maximum horizontal stress directions in the study area are extracted from earthquake focal mechanism data. The anisotropy study results in terms of shear wave splitting fast direction axes are added to the dataset to show its effect. The results show substantial variation in SHmax directions, which reflects the complicated tectonic nature of the region. Adding the shear wave splitting data improved the results’ accuracy and showed the correlation between the two quantities in the study area.